Analysis of location factors important for development Spa tourism in Srebrenica - Nezirović, Senada (Journal for Geography, 2020)
In this paper, location factors important for the development of Spa tourism in Srebrenica was analyzed. Crni Guber Spa is located at 596 meters above sea level and is the highest spa and climatic place in northeastern Bosnia. Until the beginning of the war in 1992 in Bosnia and Herzegovina, the backbone of the economic development of the municipality of Srebrenica was the development of spa tourism. Spa Crni Guber in Srebrenica was a well-known health resort for anemic diseases. The accommodation capacities of this Spa complex were damaged by the war, so this health resort is currently in stagnation. We single out the time after 1995 as a special period, because there are no conditions for tourist movements towards the Crni Guber Spa in Srebrenica. Conducted research indicates that for the launch of the Crni Guber Spa and the adequate use of medicinal waters for medical purposes, it is necessary to resolve property and legal issues related to accommodation facilities and medical equipment of this Spa as well as the issue of concessions regarding the exploitation of medicinal water. Analyzing the importance of location factors and other factors important for the development of Spa tourism, in addition to local development policy in the municipality of Srebrenica, author believes that hydrographic and climatic resources, accommodation capacities and the touristic market are of special importance. The analysis of the spatial distribution of medicinal waters presents their economic value and proposes guidelines for further use and protection of these resources. For this type of tourist activity in Srebrenica, the tourist policy of local and state authorities is of great importance, as well as the connection between tourist organizations in order to attract visitors for treatment, recreation and rest. This paper presents a contribution to theoretical and practical research for the development of Spa tourism in the municipality of Srebrenica.
Keywords: healing waters; Crni Guber Spa; planned management